Management consulting : a guide to the profession - Kubr, Milan (International Labour Office, 2002)
This is a widely recognized reference work on the state of the art of management consulting. It offers an extensive introduction to consulting: its nature, professional standards, intervention methods, behavioural rules, current developments and future perspectives.